(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Plants are always an exemplary source of drug. In fact, many of the currently available drugs were derived either directly or indirectly from the plants. Diarrhoea affects people of all ages, due to several causes- malnutrition, infection (bacterial, viral and parasitic organisms), zinc deficiency, etc. Severe diarrhoea becomes life-threatening, particularly in young children and people who are malnourished or have impaired immunity. The current study was aimed for the formulation and evaluation of herbal tablets incorporated with Strychnos potatorum and Punica granatum extracts for antidiarrhoeal activity. The tablets were prepared by wet granulation method using above plant extracts. The prepared tablets were subjected to physical evaluation like weight variation, hardness, thickness, friability and disintegration test. The accelerated stability study for the prepared formulation was carried out and reported. Invivo anti-diarrhoeal activity was evaluated by using castor oil induced diarrhoea in rats. The standard drug used for study was loperamide. Animals was divided in to five groups of 6 animals each and diarrhea was induced by administration of castor oil at a dose of 1ml/kg b.w and the tablet formulation was administered at 50 & 100mg/kg dose levels orally. The antidiarrhoeal activity was evaluated by estimating the total number of droppings, mean weight of droppings, number of wet feaces, onset time of diarrhoea. Results were analysed by oneway ANOVA followed by Dunnet’s test. Studies revealed that prepared tablet formulation at doses 50 & 100 mg/kg b.w p.o showed significant results in a dose dependent manner comparable with that of standard Lopramide 5mg/kg b.w.